Causing Factors Crimes Against the Circulation of Counterfeit Money - Rahmat M Kau (Universitas Negeri Gorontalo, 2022)
This study aims to determine the factors causing crimes against the circulation of counterfeit money. The method used in this study is an empirical legal research methodology and uses a qualitative approach to descriptive qualitative analysis techniques. The results of this study show that the factors causing crimes against the circulation of counterfeit money include economic factors, self-benefit factors, low education factors and factors of opportunities to commit crimes, environmental factors, and technological factors. In preventing the crime of circulating counterfeit banknotes in the city of Gorontalo, in this case, the police must strictly enforce and play an active role if they receive complaints from the community. The police must be able to take precautions before the perpetrators or individuals who play the opportunity circulate counterfeit money.